Improving English Vocabulary Using Gamification of Bamboozle Platform for SMPN 2 Nglegok Grade 8 - Nurlia, Ratna; Wiratno; Mulhuda, M. Ali (Journal of Development Research, 2025)
This research aims to enhance students' vocabulary mastery through gamification on Baamboozle, as traditional teaching methods often fall short in holding students’ attention. The research employs a Classroom Action Research (CAR) methodology, conducted in two cycles, involving planning, action, observation, and reflection stages. It involved 29 eighth-graders at SMPN 2 Nglegok. Pre-tests and post-tests were given to track their vocabulary progress, and also observed their engagement and participation in class. Results indicated a significant improvement in vocabulary mastery, with the percentage of students achieving the Minimum Mastery Criteria (KKM) rising from 17.24% in the pre-test, to 48,28% in the post test of cycle 1, and  to 82.76% in the post-test II. The findings suggest that gamification, through interactive and competitive elements of the Baamboozle platform, effectively increases student motivation and engagement in learning English vocabulary. This study contributes valuable insights into the integration of technology and innovative teaching methods in language education, highlighting the importance of gamification in fostering a more dynamic and enjoyable learning environment to improve vocabularies.